2021
DOI: 10.1038/s12276-020-00550-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of estrogen against excessive erythrocytosis in Monge’s disease

Abstract: Monge’s disease (chronic mountain sickness (CMS)) is a maladaptive condition caused by chronic (years) exposure to high-altitude hypoxia. One of the defining features of CMS is excessive erythrocytosis with extremely high hematocrit levels. In the Andean population, CMS prevalence is vastly different between males and females, being rare in females. Furthermore, there is a sharp increase in CMS incidence in females after menopause. In this study, we assessed the role of sex hormones (testosterone, progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…Estrogens regulate EPO, HIF1A, GATA1, VEGF , genes related to erythropoiesis and erythroid apoptosis mechanisms. [48] These findings suggest that sex hormones moderate the erythropoietic response of chronic exposure to hypoxia and may contribute to the mortality excess in male patients with COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Estrogens regulate EPO, HIF1A, GATA1, VEGF , genes related to erythropoiesis and erythroid apoptosis mechanisms. [48] These findings suggest that sex hormones moderate the erythropoietic response of chronic exposure to hypoxia and may contribute to the mortality excess in male patients with COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…The inclusion of male highlanders only is an additional limitation of our study. CMS has a very low prevalence in pre‐menopausal women (Azad et al., 2021 ; Leon‐Velarde et al., 1997 ; Leon‐Velarde et al., 2001 ), and therefore forming comparable groups covering the same age range to avoid any confounding effects of age, and of menopause itself, would have been difficult. For these and cultural reasons, women were not included in the study and therefore our findings cannot be extrapolated to female CMS highlanders.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were confirmed in vivo, where high dosage of estrogens causes anemia in humans and animal models [ 54 , 56 ]. Interestingly, it has been observed that in people living at high altitudes, females are more protected than males against chronic mountain sickness erythrocytosis (CMS or Monge’s disease); of note, the incidence of CMS clearly increases after menopause, confirming the link with estrogen levels [ 57 ]. The same study reported that ER acts by repressing GATA1, with subsequent erythroid progenitor apoptosis, as originally observed by G. Blobel and colleagues [ 58 , 59 ].…”
Section: Nrs Controlling Normal Erythropoiesismentioning
confidence: 99%